Application of unique chitosan nanoparticles as an anti-cariogenic bacterial agent in mouthwash: Physical, stability and antibacterial properties evaluation - Angelica Rae Montesines Villaseñor; Veasarach Jonjaroen; Araya Phonghanyudh; Rudee Surarit; Nuttawee Niamsiri (Research Square, 2022)
Abstract Chitosan nanoparticles have long been used as antibacterial agent in several fields due to its advantages in physiochemical characteristics. This study aimed to evaluate the different chitosan sources and crosslinkers used for fabricating chitosan nanoparticles (CNs) and to consider the application of CNs as an antibacterial agent in mouthwash. Different CNs structures were synthesized and subsequently incorporated into four different mouthwash solutions. Particle size, polydispersity index (PDI) and zeta potential of CNs were evaluated. The stability of CNs was also observed at different pH (5.0, 5.5 and 6.0) for over 2 months. At the optimal pH condition, each mouthwash formulation with CNs was tested for their antimicrobial properties against two bacterial species frequently associated with dental caries; Streptococcus mutans and Lactobacillus casei . The results showed that CNs could be synthesized from both squid- and shrimp-derived chitosan materials. When CNs-TPP was resuspended in either stock buffer or mouthwash solution often have smaller particle size compared to CNs-HMP. Among four formulations, the squid CNs-TPP mouthwash was found to be the most stable in particle size ranging from pH 5.0 to 6.0 during the 2-month period. The antibacterial results showed that the CNs-TPP were more effective in killing both S. mutans and L. casei . Our findings suggested that CNs have potential to be used as an antibacterial agent in the mouthwash formulation with high stability.
Keywords: Oral microbiology and periodontitis research; Advanced Drug Delivery Systems; Nanocomposite Films for Food Packaging